Ablation Threshold Measurement and Chemical Modification of UV Nanosecond Laser Micromachining of Polycrystalline Diamond. Issue 24 (21st December 2021) - Ullah, Naveed; Cui, Jianlei; Dong, Xiangyang; Fang, Xuyang; Dou, Jian; Sun, Zheng; Mei, Xuesong
Abstract : Polycrystalline Diamond In article number 2100450, Jianlei Cui and co‐workers study the ablation threshold and phase transition of polycrystalline diamond under the irradiation of an ultraviolet nanosecond laser with a wavelength of 355 nm. It reveals that the ablation threshold of polycrystalline diamond is approximately 3.7326 J cm −2 . Furthermore, the sp 3 structure of the diamond transforms into the sp 2 graphite phase during the ultraviolet nanosecond laser micromachining.